Feasibility, safety, and acute efficacy of the fourth‐generation cryoballoon for ablation of atrial fibrillation: Another step forward?. Issue 4 (25th February 2020) - Rottner, Laura; Mathew, Shibu; Reissmann, Bruno; Warneke, Laura; Martin, Isabell; Lemes, Christine; Maurer, Tilman; Wohlmuth, Peter; Ouyang, Feifan; Kuck, Karl‐Heinz; Metzner, Andreas; Rillig, Andreas
Abstract: Background: The second‐generation cryoballoon (CB2) is widely used for pulmonary vein (PV) isolation (PVI) in patients with paroxysmal atrial fibrillation (AF). Recently, the novel fourth‐generation CB (CB‐Advance PRO) was introduced, incorporating a shortened catheter tip. Hypothesis: The aim of this study was to evaluate the feasibility and acute efficacy of PVI using the CB‐Advance PRO. Methods: A total of 200 consecutive patients were analyzed. Hundred patients who underwent PVI due to symptomatic, drug‐refractory AF were treated with the CB‐Advance PRO (group I) and were included into this multicenter analysis. A group of 100 patients were treated with the CB2 and acted as controls (group II). Results: In total, 739 of 739 PVs (100%) were successfully isolated. There was a nonsignificant trend in the incidence of online registration of PV signals between both groups (group I: 77.9% vs group II: 71.4%, P = .09). Median time to PVI (time to isolation [TTI]) and mean total freezing time were significantly shorter when using the CB‐Advance PRO (group I: 33 [23, 50] vs group II: 40 [26, 60] seconds and group I: 166 ± 29 vs group II: 183 ± 38 seconds, P < .01). In three of 100 (3%) patients of group I and one of 100 (1%) patients of group II, a transient phrenic nerve palsy occurred ( P = .62). Conclusion: The use of the novel CB‐Advance PRO is feasible and associated with a significant reduction in mean TTI and mean total freezing time as compared to the CB2.